Proton ordering in (NH4)3H(SO4)2 at low‐temperature phase transitions. Issue 4 (23rd June 2013) - Sohn, Yoo Jung; Sparta, Karine M.; Prinz, Sebastian; Meven, Martin; Roth, Georg; Heger, Gernot
<x xml:space="preserve">Abstract</x> Single‐crystal neutron diffraction was used to investigate the H‐atom disorder in triammonium hydrogen disulfate (TAHS), (NH4)3H(SO4)2, below room temperature. Crystal structure analysis of the monoclinic phase III shows an increase of proton ordering with decreasing temperature in the (SO4)H(SO4) dimer. Moreover, the NH4+ groups on a general position begin ordering in this phase. The monoclinic unit cell of TAHS‐IV doubles in the b direction and a slight distortion of SO42− and NH4+ tetrahedra is observed. The order parameter introduced by Landau was determined for the second‐order II/III and III/IV phase transitions from the intensities of the superstructure reflections. TAHS‐V has a triclinic space group and the crystal structure seems to be completely ordered according to a structure analysis by single‐crystal X‐ray diffraction measurements. In addition, the decisive role of the dynamical disorder of different ammonium groups on successive phase transitions is discussed. Additional peaks were observed by X‐ray powder diffraction measurements at ∼ 70 K on cooling, which refers to the V/VII phase transition. These additional peaks remained up to ∼ 85 K on heating. They were described with a doubling of the unit cell along all three principal crystallographic directions.